Deubiquitinase Inhibitor b-AP15 Attenuated LPS-Induced Inflammation via Inhibiting ERK1/2, JNK, and NF-Kappa B - Zhang, Fangcheng; Xu, Ruqin; Chai, Renjie; Xu, Qiong; Liu, Mingke; Chen, Xuke; Chen, Xiaohua; Kong, Tianyu; Zhang, Chongyu; Liu, Shi-Ming; Zhang, Zhenhui; Liu, Ningning (Frontiers in Molecular Biosciences, 2020)
b-AP15 is a deubiquitinase (DUB) inhibitor of 19S proteasomes, which in turn targets ubiquitin C-terminal hydrolase 5 (UCHL5) and ubiquitin-specific peptidase 14 (USP14). Nuclear factor kappa B (NF-κB) is closely linked to cellular response in macrophages when the organism is in the state of microbial infection, and it acts as a vital part in the mechanism of inflammatory reaction. However, the molecular mechanism by which DUB inhibitors, especially b-AP15, regulates inflammation remains poorly understood. This study aimed to investigate the relationship between b-AP15 and inflammation. The results showed that b-AP15 treatment significantly reduced the amount of inflammatory indicators, such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in lipopolysaccharides (LPS)-stimulated THP-1 and macrophages. Meanwhile, similar results were obtained from in vivo experiments. In addition, b-AP15 also significantly improved the survival rate of sepsis mouse via high density LPS mediated. Furthermore, b-AP15 also inhibited the ERK1/2 and JNK phosphorylation, increased IκBα levels, and inhibited NF-κB p65 by removing them from the cytoplasm into the nucleus. All these findings suggested that b-AP15 has anti-inflammatory action, and acts as a potential neoteric target drug for treating microbial infection.